Pendampingan Manajemen Destinasi Wisata Berbasis Community-Based Tourism di Desa Wisata Sumber Nyamplung, Pandaan, Pasuruan - Siti Muyasaroh; Zainul Ahwan; Achmad Komarudin; Wahidatun Nikmah; M. Angga Maulana; Choirul Ummah (Yayasan Lentera Avanya Nagari, 2026)
Community-based village tourism development is a crucial strategy for promoting sustainable local economic independence. Tembong Hamlet, Plintahan Village, Pasuruan Regency, boasts natural tourism potential in Sumber Nyamplung, but management faces obstacles like limited human resource capacity, suboptimal institutional arrangements, and a lack of promotional strategies. This community service activity aims to increase the community's capacity to manage tourism through a community-based tourism (CBT)-based capacity-building approach. The method used is Asset-Based Community Development (ABCD), including asset identification, participatory planning, program implementation, and evaluation. The results indicate increased community participation through collective activities like cooperation (gotong royong), contributing to social capital formation and a sense of ownership. Training and mentoring successfully increased community capacity in tourism management and strengthened the role of local institutions through the Tourism Awareness Group (Pokdarwis). Furthermore, using social media as a promotional tool demonstrates adaptation to digital technology, thereby increasing destination visibility. Overall, integrating capacity building and CBT proves effective in promoting sustainable village tourism development. This program impacts social and institutional aspects while opening opportunities for strengthening the local economy. Therefore, this model serves as an alternative approach for developing community-based tourism villages in similar regions. Pengembangan desa wisata berbasis masyarakat merupakan strategi penting untuk mendorong kemandirian ekonomi lokal berkelanjutan. Dusun Tembong, Desa Plintahan, Kabupaten Pasuruan memiliki potensi wisata alam Sumber Nyamplung, namun pengelolaannya terkendala keterbatasan SDM, kelembagaan yang belum optimal, dan minimnya promosi. Kegiatan pengabdian ini bertujuan meningkatkan kapasitas masyarakat dalam mengelola wisata melalui pendekatan capacity building berbasis Community-Based Tourism (CBT). Metode yang digunakan adalah Asset-Based Community Development (ABCD) melalui tahapan identifikasi aset, perencanaan partisipatif, implementasi, dan evaluasi. Hasil pengabdian menunjukkan keberhasilan utilisasi aset fisik berupa kawasan mata air Sumber Nyamplung dan aset manusia melalui penguatan kapasitas Pokdarwis serta pemuda setempat. Pemanfaatan aset tersebut terbukti memicu peningkatan partisipasi masyarakat melalui gotong royong, yang berkontribusi pada pembentukan modal sosial dan rasa memiliki. Pelatihan dan pendampingan berhasil meningkatkan kapasitas pengelolaan wisata serta memperkuat peran kelembagaan lokal. Selain itu, pemanfaatan media sosial sebagai sarana promosi menunjukkan adaptasi teknologi digital yang meningkatkan visibilitas destinasi. Secara keseluruhan, integrasi capacity building dan CBT efektif mendorong pengembangan desa wisata berkelanjutan, berdampak pada aspek sosial-kelembagaan, serta membuka peluang penguatan ekonomi lokal. Model ini dapat menjadi alternatif pendekatan di wilayah dengan karakteristik serupa.